Open-celled silicon carbide foams with high porosity from boron-modified polycarbosilanes. Issue 16 (December 2019) - Durif, Charlotte; Wynn, Mélanie; Balestrat, Maxime; Franchin, Giorgia; Kim, Young-Wook; Leriche, Anne; Miele, Philippe; Colombo, Paolo; Bernard, Samuel
Graphical abstract: Abstract: Open-Celled silicon carbide (SiC) foams were prepared from a mixture of a boron-modified polycarbosilane as a preceramic polymer and poly(methymetacrylate) (PMMA) microbeads as sacrificial agents. The process consists in the cross-linking of the liquid allylhydridopolycarbosilane (AHPCS, SiC precursor) with borane dimethylsulfide (BDMS, boron source) to form a solid boron-modified polycarbosilane with an adjusted cross-linking degree. The latter is mixed with PMMA microbeads (25 μm) in a 20:80 ratio and the mixture is warm-pressed at 120 °C forming consolidated green bodies to be pyrolyzed at 1000 °C under argon and to deliver open-celled SiC foams with an interconnected porosity of 73.4vol %. These foams combine a low density with a compressive strength of 3.49 ± 0.56 MPa and a thermal and mechanical stability under argon up to 1300 °C. Ageing and microfiltration tests in the conditions of a primary loop of coolant in a Pressurized Water Reactor (PWR) showed that foams display a relatively high stability while retaining particles of 5 μm in diameter making these materials as appropriate candidates to work in separation techniques under harsh environments.